Difficulties in Making Diagnosis of Inflammatory Bowel Disease: Several Cases Analysis - Daldiyono Hardjodisastro; Ari Fahrial Syam (The Indonesian Society for Digestive Endoscopy, 2004)
Inflammatory bowel disease (IBD) is rarely found in clinical practice. However, the incidence of IBD seems to have increased recently. Generally, the patients will come to hospital with chief complaint of chronic diarrhea with or without hematochezia. We reported two cases of IBD in which they had been misdiagnosed as colitis tuberculosis based on colonoscopy examination. Treatment of anti tuberculosis drugs had made no clinical improvement. Further evaluation suggested the diagnosis of IBD. They responded very well clinically after treated as IBD. This case report reminds us to consider the diagnosis of IBD in patient with chronic diarrhea and ulceration in colonic mucosa at colonoscopy. Keywords: Chronic diarrhea, inflammatory bowel disease, hematochezia